External and Internal Environment, and Business Ethic on Business Partnership and its Implication on Small Enterprise Performance in West Java - Tatang Suryana; Iman Sudirman; Ellen Rusliati (Faculty of Economics and Business, University of Pasundan, 2017)
The purpose of this study is to obtain empirical evidence and find clarity on the phenomena about the influence of external and internal environment, and business ethic on business partnership and its impact on small enterprise performance in West Java on small stamped-batik business. The research was conducted by using descriptive and inductive method by taking sample of 116 companies using simple random sampling technique proportionally with structural equation model analysis. The conclusions obtained are that the external environment, and business ethic were in the fair category, while the internal environment, partnership, and performance were good. SEM analysis showed that the external and internal environment, and business ethic simultaneously had positive and significant effect on partnership of 64.6%. Partially, the external environment had positive and significant impact on the business partnership of 15.41%. The internal environment had a positive and significant impact on business partnership of 28.73%. Business ethic had a positive and significant effect on business partnership of 20.30%. Business Partnership had a positive and significant impact on Small Enterprise Performance of 84.3%.